Urban Land Uses and Smart Mobility - Francini, Mauro; Palermo, Annunziata; Viapiana, Maria Francesca (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The object of this work consists of the will to define a renewed relationship between spatial planning and transport systems, which focuses attention on road safety, whereas to date the studies on this relationship have mainly examined the transport impacts on land use. Therefore, in addition to the analysis of the physical characteristics of road infrastructure, there is a need to examine which urban land uses can generate points of risk, both in terms of attraction of vehicles and pedestrian flows as well as in terms of concentration of vulnerable road users, in order to organize a complete information and telecommunication system for road safety. In short, considering a specific testing ground, some urban land uses have been located, with relative dimensional analysis and characterization of access conditions in typological-functional terms: services (schools, healthcare structures, sports facilities); tertiary/production industry (wholesale, shopping centres, industrial sites); tourism sector (hotels, resorts, historical and cultural heritage). The collection of information, corresponding to mapping of prospective risk factors, represented the basis for the entry of specific data within a wider reference database.